The Quality Life of Matriarch and Program of Poverty Reduction in Jember Regency - Ade Ananta Pratiwi; Al Munawir; Dewi Rokhmah (Aloha International Journal of Health Advancement (AIJHA), 2020)
Introduction: Poverty was regarded as a common problem existed in many countries, either in developed countries or developing countries, even, the poverty was still a priority problem in SDGs era. In 2018 East Java was positioned on the first rank of highest level of poverty in Java, particularly Jember Regency was ranked in the second. The government of East Java has observed this poverty phenomenon on female society, which was then called as poverty feminization. Therefore, the government of East Java established a program of poverty alleviation on women, it was known as a feminization program of poverty reduction. This program aimed to provide job or job, so the matriarch would have access to several sectors, as economic, education, or health. The easy access given to the matriarch was expected to realize more quality of life. Methods: This research was categorized into quantitative research and exerted cross sectional approach. The total population in this research was taken from all women who got help from the feminization program of poverty reduction in Jember, specifically the total were about 1227 respondents. The method of sampling was purposive sampling by employing representative of data sampling in each sub-regency. The total sample in this research were 302 respondents. Further, the data was collected through instrument of WHOQOL-BREF questionnaire, while the data was analyzed through Spearman correlation method. Results: According to the result of data analysis on factor of job to the life quality, it was obtained p-value of 0.000, which referred the correlation between job and life quality of matriarch. Moreover, the data analysis on factor of income to the life quality, it was obtained p-value of 0.000, which referred the relation between income and life quality of matriarch. Conclusion: There was a relation between job as well as income and the life quality of matriarch. Keywords: matriarch; feminization of poverty; job; income; life quality